Driving Performance in Patients With Idiopathic Cervical Dystonia; A Driving Simulator Pilot Study - van den Dool, J.; Visser, B.; Huitema, R. B.; Caljouw, S. R.; Tijssen, M. A. J. (Frontiers in Neurology, 2020)
Objective: To explore driving performance and driving safety in patients with cervical dystonia (CD) on a simulated lane tracking, intersections and highway ride and to compare it to healthy controls. Design: This study was performed as an explorative between group comparison. Participants: Ten CD patients with primary CD, 30 years or older, stable on botulinum toxin treatment for over a year, holding a valid drivers’ license and being an active driver were compared with ten healthy controls, matched for age and gender. Main outcome measures: Driving performance and safety, measured by various outcomes from the simulator, such as the standard deviation of the lateral position on the road, rule violations, percentage of line crossings, gap distance and number of collisions. Fatigue and driving effort were measured with the Borg CR-10 scale and self-perceived fitness to drive was assessed with Fitness to Drive Screening. Results: Except for a higher percentage of line crossings on the right side of the road by controls (median percentage 2.30, range.00-37.00 vs .00, range .00-9.20, p=.043), no differences were found in driving performance and driving safety during the simulator rides. Fatigue levels were significantly higher in CD patients just before (p=.005) and after (p=.033) the lane tracking ride (patients median fatigue levels before 1.5 (range 0.00 to 6.00) and after 1.5 (range 0.00 to 7.00) vs controls median fatigue levels before and after 0.00 (no range). No significant differences were found on self-perceived fitness to drive. Conclusion: In patients with CD there were no indications that driving performance or driving safety were significant different from healthy controls in a simulator. Patients reported higher levels of fatigue both before and after driving compared to controls in accordance with the non-motor symptoms known in CD.